Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Interpretable mapping of fine-grained urban building functions from street-view images using foundation models - Jiaming Sun; Wei Yang; Tingting Xu; Zongshun Tian; Yongchuan Zhang; Mengjia Yin (Computers, Environment and Urban Systems, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Transport Pathway Evolution and Retention Dynamics of Escherichia Coli in Homogeneous and Heterogeneous Porous Media - Yuanyuan Jia; Zhipeng Tu; Wenjing Zhang; Shutong Jiang; Jiaming Sun; Bo Wan (Transport in Porous Media, 2026)

Maternal Stress During Pregnancy Induces Higher Anxiety-Like Behavior in Male Mice Offspring Under Acute Stress by Upregulating CRF/CRFR1 and Driving Time-Specific Activation of the MHb-IPN Circuit - Yujie Wang; Jiajia Zhao; Yueyang Wang; Zhixin Du; Li Wang; Zibo Ma; Siyang Sun; Xinyang Qu; Xiaohan Geng; Jiaming Yan; Liping Yang; Junlin Hou (Neuroscience Bulletin, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Two-terminal ferroelectric memristors: material innovation, mechanistic breakthroughs, new opportunities for intelligent computing - Jiaming Zhang; Chaocheng Sun; Yan Jing; Yifei Pei; Jianbin Xu; Xiaobing Yan; Jianhui Zhao (Science Bulletin, 2026)

Synergistic architecture and dynamic adaptability in heterogeneous catalysts for CO2 hydrogenation - Jiao Liu; Xingyi Cen; Jiaming Lin; Junrong Yue; Duo Sun; Fang Wang (Journal of Environmental Sciences, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

How built environments shape leisure jogging styles: Nonlinear and interactive effects across objective and subjective dimensions - Wei Yang; Mengjia Yin; Longyang Huang; Jiaming Sun; Caixuan Guo; Xin Fan; Jingjing Li (Journal of Transport Geography, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Efficacy and Safety of OnabotulinumtoxinA for the Treatment of Masseter Muscle Prominence in a Chinese Population: 6-Month Results From a Phase 3, Randomized, Placebo-Controlled Study - Jiaming Sun; Yuejun Li; Tianjiao Yang; Jia Chang (Toxicon, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Prediction of Heterogeneous Shale Lithology in the Kaijiang–Liangping Trough Based on Dream Optimization Algorithm and Support Vector Machine - Lexin Yuan; Zhiming Xu; Haofei Sun; Jungang Lu; Luchuan Zhang; Xiangdong Yin; Jiaming Li (Mathematical Geosciences, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

QACO: An adaptive multi-phase ant colony optimization approach for robust feature selection - Zihang Wang; Ye Liang; Wenwei Sun; Jiaming Liu (Swarm and Evolutionary Computation, 2026)

Evaluating aeration rate modulation to restructure denitrifier communities for nitrous oxide mitigation in cattle manure composting using a novel integrated analytical framework - Yu Sun; Xiran Zhou; Jiaming Fan; Lei Sun; Shuai Shi; Xiuhong Xu (Journal of Environmental Management, 2026)

Potential strategies of natural products in the treatment of atherosclerosis: Focusing on modulating macrophage polarization - Wenjie Zhao; Peng Sun; Jiaming Huan; Lei Zhang; Shijing Peng; Tong Jiang; Linghui Kong; Xinghao Zhu; Wenqing Yang; Dongmei Qi; Yunlun Li (PharmaNutrition, 2025)

Thermophilic antagonistic/competitive networks drive low nitrogen loss in Phase I commercial composting: Deciphering microbe-nitrogen coupling using the novel multistep interaction validation analysis - Yu Sun; Jiaming Fan; Yue Zhang; Zhaoxue Gai; Shuai Shi; Xiuhong Xu (Journal of Environmental Chemical Engineering, 2025)

Convenient DNA extraction integrated with dual RPA-LFA technology for simultaneous detection of Salmonella and Listeria monocytogenes - Jiaming Huang; Jing Sun; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Yingjian Lu (Food Bioscience, 2025)

CRISPR/Cas12b-mediated one-tube live cell assay facilitates Salmonella typhimurium detection in poultry meat - Yongjin Dai; Jiaming Huang; Moran Zhang; Xinyi Pang; Xiangfei Li; Jing Sun; Yingjian Lu (Food Bioscience, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

Torsional Deformation of Existing Tunnels Induced by Obliquely Undercrossing Shield Tunneling - Jiaming Ou; Xiaochun Zhong; Lisu Sun; Wei Wang (Geotechnical and Geological Engineering, 2025)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

Hybrid fabrication of perfusable stiffness-flexible integrated scaffold mimicking hierarchical tubular bone - Yifan Zhang; Zhipeng Li; Bingkun Bao; Jingyi Ju; Wenbin Jiang; Linyong Zhu; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Large-area crack-free photonic crystals coating on leather with brilliant and robust iridescent structural color - Jingyuan Hu; Yaqun Han; Xin Sun; Wenbo Wu; Jiaming Huyan; Suli Wu (Chemical Engineering Journal, 2025)

Study on rockburst control of deep-buried tunnel by combining advanced stress release borehole and hydraulic fracturing - Jiaming Li; Shibin Tang; Tianjiao Li; Shuguang Zhang; Liexian Tang; Kang Sun (Tunnelling and Underground Space Technology, 2025)

Ultrasensitive nanoenzymes-based lateral flow immunoassay platform for accurate detection of folic acid in human serum - Jinbo Cao; Tiemei Li; Xianglin Liao; Jiaming Zhang; Xixiang Yang; Huiqi Yan; Boyang Sun; Yanfei Li; Jiaxiang Huang; Yao Wang; Xiaogang Hu; Li Wang (Chemical Engineering Journal, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

Interface catalysis over AlPO4/Al2O3 with F-Al-O species for resource utilization of hydrofluorocarbon greenhouse gas - Yiwei Sun; Xiaoli Wei; Fangcao Liu; Bing Liu; Jiaming Zhao; Yubao Bi; Wenfeng Han (Journal of Environmental Chemical Engineering, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Enhanced steam reforming of benzene in a two-stage catalytic system: Insights into metal synergies and carbon deposition evolution - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Yuan Sun (Fuel, 2025)

Haversian bone mimicking scaffold with built-in vasculature for bone tissue engineering - Jian Liu; Zhen You; Xinmei Li; Boyang Zhang; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Soil infiltration mechanisms under plant root disturbance in arid and semi-arid grasslands and the response of solute transport in rhizosphere soil - Yuanyuan Jia; Huan Huan; Wenjing Zhang; Bo Wan; Jiaming Sun; Zhipeng Tu (Science of The Total Environment, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Rapid and accurate AuNPs-sodium deoxycholate-propidium monoazide-qPCR technique for simultaneous detection of viable Listeria monocytogenes and Salmonella - Jiaming Huang; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Jing Sun; Yingjian Lu (Food Control, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Carbonate system in the subtropical Jiulong River Estuary and CO2 flux estimation under modulation of tidal cycle - Weicong Chen; Heng Sun; Zhongyong Gao; Jiaming Lin; Min Xu; Aijun Wang; Shuqin Tao (Acta Oceanologica Sinica, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Hydrocarbon Source and Relationship between Hydrocarbon Charging Process and Reservoir Tight Period of the Denglouku Formation Tight Sandstone Gas Reservoirs in the Xujiaweizi Fault Depression, Songliao Basin - Huan Miao; Zhenxue Jiang; Jiaming Lu; Chengju Zhang; Lidong Shi; Lidong Sun; Liang Yang; Peng Shang (Natural Resources Research, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

Effects of polymerization types on plastics ingestion and biodegradation by Zophobas atratus larvae, and successions of both gut bacterial and fungal microbiomes - Yue Weng; Xiaoyu Han; Huayang Sun; Jiaming Wang; Yumeng Wang; Xin Zhao (Environmental Research, 2024)

PcPME63 is involved in fruit softening during post-cold storage process of European pear (Pyrus communis L.) - Beibei Cao; Rongxiang Zhu; Manyi Sun; Bobo Song; Jun Wu; Jiaming Li (Postharvest Biology and Technology, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

The relationship between repeated impacts and CAI strength of sandwich structure considering different impactor shape in individual impact - Keyu Zhu; Xitao Zheng; Jiaming Sun; Guoyue Wang; Leilei Yan (Engineering Structures, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Recent advances in nanomaterial-enhanced persulfate activation for organic pollutants removal: Electron transfer, surface reactions, and radical generation - Dingren Ma; Ji Mei; Qiwen Liang; Yimu Jiao; Tianyu Hu; Jingchen Chen; Jiaming Wang; Hao Zhou; Qiyu Lian; Mingzhe Sun; Dehua Xia; Tianqi Wang (Journal of Environmental Chemical Engineering, 2023)

Investigation of Mechanical Properties of Quartz and Illite in Shale Using Molecular Dynamics Simulation - Shuang Liang; Mingyu Gao; Shuo Sun; Yikun Liu; Wanxin Li; Jingkun Wang; Jiaming Wang; Chengfeng Yin (Natural Resources Research, 2023)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Revealing the spatio-temporal characteristics and impact mechanism of carbon emission in China's urban agglomerations - Ziyi Wang; Jingxiang Zhang; Pingjia Luo; Dongqi Sun; Jiaming Li (Urban Climate, 2023)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Self-powered health monitoring with ultrafast response and recovery enabled by nanostructured silicon moisture-electric generator - Yuhang Song; Chang Shu; Zheheng Song; Xuelian Zeng; Xianrong Yuan; Yanan Wang; Jiaming Xu; Qianyue Feng; Tao Song; Beibei Shao; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Improving the prediction accuracy of small-strain shear modulus of granular soils through PSD: An investigation enabled by DEM and machine learning technique - Xingyang Liu; Zhanchao Li; Degao Zou; Linsong Sun; Khailah Ebrahim Yahya; Jiaming Liang (Computers and Geotechnics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Discovery of the Early Paleozoic Akechukesai high-Mg diorites in the western segment of East Kunlun Orogenic Belt and its constraints on the mechanism of break-off from Proto-Tethys oceanic subducted slab - Chao Wang; Fengyue Sun; Dongwei Liu; Lei Zuo; Tuofei Zhao; Jiaming Yan (Geosciences Journal, 2022)

Characteristics of PAHs in soils under different land-use types and their associated health risks in the northern Taihu Basin, China - Tian Sun; Yanhua Wang; Jiaming Tian; Xinggong Kong (Journal of Soils and Sediments, 2022)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

Large-Scale Test Model of the Progressive Deformation and Failure of Cracked Soil Slopes - Zhi Zhou; Jiaming Zhang; Fulong Ning; Yi Luo; Lily Chong; Kuangbiao Sun (Journal of Earth Science, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Deguan Tan; Bingying Han; Xuepiao Sun; Jiaming Zhang (Physiology and Molecular Biology of Plants, 2020)

Geochronology, Geochemistry, and Hf Isotopic Compositions of Monzogranites and Mafic-Ultramafic Complexes in the Maxingdawannan Area, Eastern Kunlun Orogen, Western China: Implications for Magma Sources, Geodynamic Setting, and Petrogenesis - Jiaming Yan; Guosheng Sun; Fengyue Sun; Liang Li; Haoran Li; Zhenhua Gao; Lei Hua; Zhengping Yan (Journal of Earth Science, 2019)

Gene coexpression analysis reveals dose-dependent and type-specific networks responding to ionizing radiation in the aquatic model plant Lemna minor using public data - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Xuepiao Sun; Jiaming Zhang (Journal of Genetics, 2019)

Comparative morphology of in vivo and in vitro laticiferous cells and potential use of in vitro laticifers in early selection of rubber tree clones - Deguan Tan; Anuwat Kumpeangkeaw; Xuepiao Sun; Weiguo Li; Yiming Zhu; Jiaming Zhang (Trees, 2019)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Rapid and highly efficient callus induction and plant regeneration in the starch-rich duckweed strains of Landoltia punctata - Meng Huang; Lili Fu; Xuepiao Sun; Rong Di; Jiaming Zhang (Acta Physiologiae Plantarum, 2016)

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Shuai Ma; Bingyin Han; Volker A. R. Huss; Xiaowen Hu; Xuepiao Sun; Jiaming Zhang (Hydrobiologia, 2015)

Age-dependent and jasmonic acid-induced laticifer-cell differentiation in anther callus cultures of rubber tree - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Planta, 2014)

Clinical Analysis of 15 Cases of Liver Nodular Regenerative Hyperplasia - Tao Guo; Jiaming Qian; Liming Zhu; Weixun Zhou; Feng Zhu; Gang Sun; Xiucai Fang (Cell Biochemistry and Biophysics, 2012)

Histochemical and immunohistochemical identification of laticifer cells in callus cultures derived from anthers of Hevea brasiliensis - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Plant Cell Reports, 2011)